2015
DOI: 10.1016/s1473-3099(15)70007-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two-dose priming plus 9-month booster with a standard three-dose priming schedule for a ten-valent pneumococcal conjugate vaccine in Nepalese infants: a randomised, controlled, open-label, non-inferiority trial

Abstract: This study was supported by funding from the National Institute for Public Health and the Environment, The Netherlands; Oxford Vaccine Group, University of Oxford, UK; and GlaxoSmithKline Biologicals, Belgium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Our findings are similar to those from a study in Nepal where PHiD-CV was administered as a 2 + 1 (6, 14 weeks, and 9 months) or 3 + 0 (6, 10, 14 weeks) schedule [18]. At age 18 weeks, the 2 + 1 and 3 + 0 groups did not differ in percentages of children with IgG concentrations ≥0.2 μg/mL or with OPA titers ≥8 for any of the PHiD-CV serotypes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are similar to those from a study in Nepal where PHiD-CV was administered as a 2 + 1 (6, 14 weeks, and 9 months) or 3 + 0 (6, 10, 14 weeks) schedule [18]. At age 18 weeks, the 2 + 1 and 3 + 0 groups did not differ in percentages of children with IgG concentrations ≥0.2 μg/mL or with OPA titers ≥8 for any of the PHiD-CV serotypes.…”
Section: Discussionsupporting
confidence: 89%
“…In a resource-limited setting in Nepal, the use of a 2 + 1 PHiD-CV schedule with primary doses at 6 and 14 weeks and a booster at age 9 months improved antibody persistence through early childhood without compromising antibody responses in early infancy (i.e. postprimary vaccination) relative to a 3 + 0 PHiD-CV schedule with primary doses at 6, 10, and 14 weeks [18].…”
Section: Introductionmentioning
confidence: 98%
“…Sample sizes were based on a prior study in which, at 9 months of age, there were 5 out of 10 serotypes with serotype-specific IgG ≥ 0.2 μg/mL (measured by the GSK ELISA) in at least 93% of participants. 6 We used a WHO reference laboratory ELISA in this study; measures of 0•2 μg/mL in the GSK ELISA correlates with 0•35 μg/mL in the WHO ELISA. Assuming the same response, 304 participants would provide 90% power (α=0•025) to determine if the 6+10 schedule was non-inferior to the 6+14 schedule in 5 out of 10 serotypes, and 80% power to determine if the 6+10 schedule was non-inferior to the 6+14 schedule in 7 out of 10 serotypes.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…4,5 Surveillance conducted since 2005 at Patan Hospital, Kathmandu indicates the majority of IPD is due to serotypes 1, 5 and 14, and that the majority of IPD occurs in late infancy and toddlerhood. [5][6][7] The ten-valent pneumococcal conjugate vaccine (PCV10) was introduced into the routine infant immunization schedule of Nepal during 2015. 8 A randomised controlled trial, conducted at Patan Hospital, assessing the immunogenicity of PCV10, demonstrated that a two-dose prime (at 6 and 14 weeks) with a 9-month booster was non-inferior for IgG concentrations at 18 weeks and 10 months and superior at 2-4 years of age when compared with a conventional three-dose priming only schedule (6, 10, and 14 weeks).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation